The Effects of Contamination and Cleanup on Commercial and Industrial Properties: A Hedonic Pricing Model of Maryland and Baltimore City - Anna Alberini; Alberto Longo (European Regional Science Association (ERSA), 2006)
This paper applies the travel cost method to visits to cultural sites in Armenia by domestic visitors. Respondents intercepted at four cultural monuments provided information on their visitation patterns, experience at the site, perception of the state of conservation of the monuments, and rating of the quality of the services and infrastructures. We combine actual trips with stated trips under hypothetical programs that would enhance the conservation of the monuments and improve one of (i) the cultural experience at the site, (ii) the quality of the infrastructure, or (iii) the quality of the services, and use the combined actual and stated trips to fit a panel data model. Our investigation shows that that there are significant use values associated with the four study monuments, and that conservation programs and initiatives that improve the cultural experience, or simply make it easier for the respondent to reach and spend time at the monument, are valued by domestic visitors and would encourage higher visitation rates.
Keywords: 330